Application of Rice-Corn Intercropping as an Optimization of the Land Use Utilization and Increasing of Farmer Income in Playen, Gunungkidul - Riyanto Damasus; Yustisia; Anshori Arif; Srihartanto Eko (E3S Web of Conferences, 2021)
Intercropping is an attempt to plant several types of crops on the land at the same time, arranged in such a way in a row of plants. Planting in this way can be done on two types of plants that are relatively different old. The application of Rice-Corn intercropping was carried out in Playen District of Gunungkidul. Rice seed was used Sidenuk and Inpari 42 varieties then planted at distance of 40 cm x 20 x 12.5 cm (Tajarwo 2:1). The corn seed used Pioneer 35 and they are planted at 60 cm x 25 cm. The purpose of this research is to examine the application of intercropping rice-corn compared to monoculture cultivation on the aspects of soil nutrients status, affects intercropping on both crops yield and feassibility analisys of the intercropping farming on the two different agricultural system. The results of study show that on intercropping pattern rice yield can reach 5.19 to 5.85 ton ha-1 and dry corn shells from 5.43 to 6.28 tons ha-1 and quite profitable with a B/C ratio of 2.68 and R/C ratio of 3.12 compared to rice or corn monoculture planting patterns alone with B/C ratios of 1.24 and 1.88, respectively